2021
DOI: 10.1002/ppul.25286
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary eosinophilic vasculitis with granulomas and benralizumab in children

Abstract: Letter to the Editor, Pulmonary eosinophilia represents a group of heterogeneous disorders consisting of lung disease and eosinophilia in the peripheral blood, alveoli, and/or pulmonary interstitium. 1 Subtype classifications include eosinophilic pneumonia (acute and chronic), allergic bronchopulmonary aspergillosis (ABPA), eosinophilic granulomatosis with polyangiitis (EGPA), drug or parasite-induced pulmonary eosinophilia, hypereosinophilic syndromes, and idiopathic pulmonary eosinophilia. 1 These classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In Supplementary Table S5 , we report off-label use of Benralizumab in children with pulmonary eosinophilia, which represents a group of heterogeneous disorders consisting of lung disease and eosinophilia in the peripheral blood, alveoli and/or pulmonary interstitium [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Supplementary Table S5 , we report off-label use of Benralizumab in children with pulmonary eosinophilia, which represents a group of heterogeneous disorders consisting of lung disease and eosinophilia in the peripheral blood, alveoli and/or pulmonary interstitium [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our case supports the growing evidence for the use of benralizumab in the treatment of EGPA. Most studies have reported its efficacy in the treatment of patients with pulmonary eosinophilia and eosinophilic asthma 9,11 . It seems that benralizumab may also improve the skin lesions associated with EGPA, including in paediatric patients with this condition.…”
Section: Discussionmentioning
confidence: 99%
“…One month later, symptom control was achieved 18 . Interestingly, another humanized monoclonal antibody, benralizumab, which binds to IL‐5 receptors, has very recently been shown to impart beneficial effects in three pediatric patients with pulmonary eosinophilia 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 Interestingly, another humanized monoclonal antibody, benralizumab, which binds to IL-5 receptors, has very recently been shown to impart beneficial effects in three pediatric patients with pulmonary eosinophilia. 19 Our patient's clinical diagnosis of EGPA in 2014 was based on the criteria published in 1990 by The American College of Rheumatology. Specifically, four of the following six criteria must be fulfilled and our patient got four of them (asthma, peripheral blood eosinophilia, pulmonary infiltrates, sinusitis).…”
Section: Discussionmentioning
confidence: 99%